ANALISIS BIAYA-MANFAAT DAN APLIKASI MODEL PENERIMAAN TEKNOLOGI PADA KEPUTUSAN OUTSOURCING TI - Rahmiati, Rahmiati (Faculty of Economics and Business Universitas Jenderal Soedirman, 2009)
Information technology outsourcing continues to advance. Outsourcing can be success if it’s done for the right reason, follow due process, and it pursued with realistic expectation and a clear understanding of where the benefits are likely to emerge. Although interest to outsourcing arise, but many companies have no a clear understanding about the consequency. This article try to give an overview about cost, risk and benefit of Information Technology outsourcing